PERFORMANCE AND LEVELS ANALYSIS OF POLLUTANT EMISSIONS WHEN USING BIOFUELS IN THE PT6 ENGINE - Mónico Muñoz, Luisa Fernanda; Avella , Richard Giovanni; Gonzalez Cruz, Francisco Javier (Journal of Applied Engineering Science, 2024)
The Aircraft use jet engines, which have been op-timized over the years to be more efficient, silent, generate higher performance and emit lower levels of polluting emissions. However, there is still a high dependence on fossil fuels, for which high-lights the need to strengthen the study of alterna-tive fuels such as hydrogen and biofuels. To investigate the benefits of some biofuels, the different performances and emissions of biodiesel were theoretically studied in one of the most widely used engines in Colombia, the PT6-A. The results indicate that the use of this biofuel reduces NOX levels and maintains engine performance at ac-ceptable levels. Analytical studies also indicate that the behavior of NOX levels is approximately quadratic in the studied interval and CO2 produc-tion is directly proportional to the percentage of biofuel in the blends.
Keywords: PT6, performance, pollutant emissions, reaction engine